Measuring "high-quality development" and progress toward "common prosperity" in China - Zhang, Junlai; Chen, Simiao; Prettner, Klaus (Social indicators research, 2025)
In 2017, the 19th National Congress of the Communist Party of China introduced the concept of "high-quality development" to shift China’s focus from high-speed growth to a more inclusive concept. In August 2021, the Chinese leadership emphasized "common prosperity" as an essential goal for modernization. However, measuring "common prosperity" in the context of "high-quality development" is challenging and requires reliable and practical indicators. Apart from income, such indicators should include other important aspects of human well-being and they should be easy to calculate and interpret. To this end, we build on recent research and use Lifetime Income (LI), Inequality-Adjusted Lifetime Income (ILI), Healthy Lifetime Income (HLI), and Inequality-Adjusted Healthy Lifetime Income (IHLI) for the first time to assess China’s performance. We calculate the four indicators for China for the period 1990 to 2019 at a national level and employ the ILI indicator at a provincial level for the years 1998, 2008, and 2018. In addition, we calculate the LI indicator for all 31 of Mainland China’s provinces for the years 1990, 2000, 2010, and 2020. Compared with other indicators such as the Human Development Index, the measures we use: (i) take into account health and equality as important components of well-being; (ii) have a mathematically defined unit of measurement that allows for a straightforward interpretation; (iii) do not depend on arbitrary weights; (iv) are able to capture tradeoffs that follow directly from their definitions; (v) are not mathematically bounded from above; and (vi) come with limited data requirements. We show that progress towards "common prosperity" was remarkable from 1990 to 2020, but there is still substantial inequality across Chinese provinces. Finally, we discuss several policy measures that could foster "common prosperity".
Gesehen am 06.11.2025